Increase in soil organic carbon in a Mollisol following simulated initial development from parent material. (January 2017) - You, M.; Li, N.; Zou, W.; Han, X.; Burger, M.
Abstract : Better understanding of the effects of land use and agricultural management on organic carbon (C) sequestration is needed to optimize the restoration of fertility in degraded soil, maintain agricultural sustainability and mitigate emissions of greenhouse gases with C sequestration. Most current studies of C sequestration focus on mature soil, whereas there has been little research on soil development from C‐poor parent material. The aim of this study was to assess soil organic carbon (SOC) stocks and C sequestration rates during the early stages of development of a Mollisol from parent material under different types of vegetation, fertilizer application regimes and organic matter inputs, and to compare the results with C sequestration of a mature Mollisol under similar management. Carbon stocks were recorded from 2004 to 2012 in the parent material of a Mollisol under natural fallow (NatF), alfalfa ( Medicago sativa L.) (Alfa) or soya beans ( Glycine max (Merrill.) L.) and maize ( Zea mays L.) (S–M) rotations with and without fertilizer application and crop residues returned or removed at harvest. There was a positive non‐linear relation between C inputs and SOC stocks; increases in SOC stocks decreased with larger additions of C. After 8 years of treatments, the SOC stocks at 0–20‐cm depth had increased in the order S–M + fertilizer + all residues returned (61%) > Alfa (60%) > S–M + fertilizer + part of residues returned (50%) > NatF (30%) > S–M + fertilizer without residue return (17%) > S–M without fertilizer or residue return (7%). These increases in SOC stocks corresponded to annual C sequestration rates of 0.02–0.83 Mg C ha −1 year −1 . In contrast, SOC stocks in the 0–20‐cm layer of the mature Mollisol changed little under similar treatments in a wheat ( Triticum aestivum L.)–maize–soya bean rotation. Our results have practical implications for how vegetation and agricultural practices could be used to optimize soil restoration and C sequestration in a temperate continental monsoon climate. Highlights : What management practices and vegetation lead to carbon sequestration during soil development? Use of a subsoil (parent material) to study soil development. Carbon stocks increased as much in alfalfa as in soya bean–maize rotations with residue return. Perennial legume systems sequester carbon comparable to annual systems with larger carbon inputs.